Handling Children with Special Needs Through Motor Activities - Tri Rukmana; Suyadi Suyadi; Siti Sri Rahayu; I'in Anggryani; Muarofakh Muarofakh (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2022)
The teacher can identify any child with a disability or special need. This is quite difficult for the teacher when the child is disturbed. Children will have difficulty learning, experience delays in doing tasks or activities, and have difficulty adjusting to the surrounding environment. The purpose of this study is to describe the efforts made by teachers in dealing with children with special needs in Al-Kindi Kindergarten. This type of research is qualitative with analytical techniques using an interactive engineering model. In this study, data analysis has been carried out simultaneously with the data collection process in the form of interviews, observations, and documentation. The object of this study was four children and four accompanying teachers. The results showed that the efforts made by teachers in dealing with children with special needs gave good results, including giving more attention to children, providing special classes for children, adding special activities for children, and providing special checks (assessments). From this study, it can be concluded that the efforts made by the teacher are effective in dealing with children with special needs who experience concentration disorders and are deaf.